Antifibrotics and Antioxidants of Chlorogenic Acid Inhibits Toll- Like Receptors-4 as Liver Fibrotic Marker - Naibey, Rosdiana; Wasityastuti, Widya; Anggorowati, Nungki; Arfian, Nur (Green Medical Journal, 2021)
Introduction: Chlorogenic Acid (CGA) is an antifibrotic and antioxidant for fibrotic tissues. These double roles be able to inhibit or fibrotic tissues chains because of internal and external issues. For example, virus, bacteria or other pathogens and also by drugs, alcohol, cigarettes, etc. as external factor that affect quality of body tissues. Toll-Like Receptor-4 (TLR-4) as a marker fibrotic tissues. It is a key for researcher could be find out by expression performance. The aim of this study is to reveal the CGA as a candidate of antifibrotic & antioxidant in liver fibrosis that induced by CCL4. Methods: This is a pure experimental research with a simple experimental design or post-test only control group design. The total 29 mices of 2.5-month-old male Swiss mices with weigh 35-40 gram divided into 6 group: 3 groups of controls (injected by natrium chloride, CGA, and CCL4) and 3 groups of treated (injected by CGA doses 42 mg/kg, 63 mg/kg or 84 mg/kg). Liver organ was used to examine the expression of TLR-4 by rt-PCR. This research revealed that expression of TLR-4 lower than the CCL4 control group (respectively, p=0.042; p=0.005; p=0.006; and p=0.001). Higher dose of CGA showed greater ability as anti-fibrotic through inhibit the expression of TLR-4. Some research found the expression of TLR-4 has been decreased by treatment of Clorogenic Acid (CGA). Conclusion: To sum up, CGA has double roles to repair liver fibrotic tissues. The greater doses of CGA, the stronger inhibition of TLR-4 expression.